Ulam-Hyers stability and existence results for a coupled sequential Hilfer-Hadamard-type integrodifferential system - Muthaiah, Subramanian; Murugesan, Manigandan; Awadalla, Muath; Unyong, Bundit; Egami, Ria H. (AIMS mathematics, 2024)
This study aimed to investigate the existence, uniqueness, and Ulam-Hyers stability of solutions in a nonlinear coupled system of Hilfer-Hadamard sequential fractional integrodifferential equations, which were further enhanced by nonlocal coupled Hadamard fractional integrodifferential multipoint boundary conditions. The desired conclusions were obtained by using well-known fixed-point theorems. It was emphasized that the fixed-point technique was useful in determining the existence and uniqueness of solutions to boundary value problems. In addition, we examined the solution's Ulam-Hyers stability for the suggested system. The resulting results were further demonstrated and validated using demonstration instances.